Strategi Pengembangan Industri Kreatif Di Kampung Batik Sokaraja Kabupaten Banyumas - Qonita, Rizka Ayu; Pribadi, Indah Ayu Permana; Sutikno, Chamid; Amanda, Ariesta; Millata, Chanifia Izza (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze the creative industry development strategy in Kampung Batik Sokaraja, Banyumas Regency. The research method used is qualitative with descriptive analysis, where data is collected through observation, interviews, and documentation. The results of the study indicate that: (1) the number of creative workers is still low compared to other sectors, so the formulation of creative resources requires improvement; (2) there is collaboration between business actors and institutions in the development of the creative industry; (3) existing infrastructure and technology are not functioning optimally and require additional investment; and (4) digital marketing strategies are needed to expand market reach. This study is expected to contribute to the development of more effective strategies for the creative industry in Kampung Batik Sokaraja. (5) The evaluation of the development strategy for the creative industry in Kampung Batik Sokaraja reveals that a comfortable and clean work environment boosts productivity and batik quality, while regular meetings foster collaboration and innovation, necessitating adaptation to market trends, new designs, and high-quality materials to enhance market competitiveness.